Setting up social experiments: the good, the bad, and the ugly - Burt S. Barnow (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2010)
It is widely agreed that randomized controlled trials - social experiments - are the gold standard for evaluating social programs. There are, however, many important issues that cannot be tested using social experiments, and often things go wrong when conducting social experiments. This paper explores these issues and offers suggestions on ways to deal with commonly encountered problems. Social experiments are preferred because random assignment assures that any differences between the treatment and control groups are due to the intervention and not some other factor; also, the results of social experiments are more easily explained and accepted by policy officials. Experimental evaluations often lack external validity and cannot control for entry effects, scale and general equilibrium effects, and aspects of the intervention that were not randomly assigned. Experiments can also lead to biased impact estimates if the control group changes its behavior or if changing the number selected changes the impact. Other problems with conducting social experiments include increased time and cost, and legal and ethical issues related to excluding people from the treatment. Things that sometimes go wrong in social experiments include programs cheating on random assignment, and participants and/or staff not understanding the intervention rules. The random assignment evaluation of the Job Training Partnership Act in the United States is used as a case study to illustrate the issues.
Keywords: 330; arbeitsmarktpolitische Maßnahme - Erfolgskontrolle; Experiment; Wirkungsforschung; wissenschaftliche Begleitung; Methodologie; Stichprobenverfahren; Stichprobenfehler; USA